2013
DOI: 10.1016/j.scitotenv.2013.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Application of green zero-valent iron nanoparticles to the remediation of soils contaminated with ibuprofen

Abstract: Zero-valent iron nanoparticles (nZVIs) are often used in environmental remediation. Their high surface area that is associated with their high reactivity makes them an excellent agent capable of transforming/degrading contaminants in soils and waters. Due to the recent development of green methods for the production of nZVIs, the use of this material became even more attractive. However, the knowledge of its capacity to de-grade distinct types of contaminants is still scarce. The present work describes the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(81 citation statements)
references
References 25 publications
6
72
0
3
Order By: Relevance
“…Once more it can be concluded that different extracts with similar antioxidant capacities can interact differently with the nZVIs, also affecting their reactivity. This is supported by Machado et al (2013b) who observed that the extracts of pear and lemon leaves have low antioxidant capacities, but in this work they presented very different reactivities. Huang et al (2014) evaluated the reactivity of nZVIs synthesized using three different tea leaves (green, oolong and black) and also observed different behaviors that were attributed to the caffeine/polyphenol content that acted as both reducing and capping agents.…”
Section: Nzvi Reactivitysupporting
confidence: 71%
See 3 more Smart Citations
“…Once more it can be concluded that different extracts with similar antioxidant capacities can interact differently with the nZVIs, also affecting their reactivity. This is supported by Machado et al (2013b) who observed that the extracts of pear and lemon leaves have low antioxidant capacities, but in this work they presented very different reactivities. Huang et al (2014) evaluated the reactivity of nZVIs synthesized using three different tea leaves (green, oolong and black) and also observed different behaviors that were attributed to the caffeine/polyphenol content that acted as both reducing and capping agents.…”
Section: Nzvi Reactivitysupporting
confidence: 71%
“…To evaluate the agglomeration behavior of the green nZVI the following tests were performed: the different nZVIs were produced according to the most favorable conditions (extraction temperature, contact time and mass of leaves:solvent volume ratio) described in Machado et al (2013b), and their agglomeration (settlement) was monitored through spectrophotometric analysis for 90 min, considering the time of the highest reactivity of nZVI. With these tests it was possible to identify which was the nZVI concentration, for each extract used, at which the settling occurred after 90 min, therefore guaranteeing that the nZVIs were in suspension during their reactive period.…”
Section: Nzvi Agglomeration Tendencymentioning
confidence: 99%
See 2 more Smart Citations
“…The degradation process in sandy soil was slower than that in aqueous solution due to the time required for percolation. The combination of these nanoparticles in a Fenton reaction showed improved efficiency up to 95 % [131].…”
Section: Heterogeneous Fenton Reactions Using Modified Iron Nanopartimentioning
confidence: 99%